Health consequences of youth sport specialization - Jayanthi, N. E.; Post, E. G.; Laury, T. C.; Fabricant, P. D. (Journal of Athletic Training, 2019)
Sport specialization is a training method now commonly used by young athletes who hope to achieve elite-level success. This may be defined as (1) choosing a main sport, (2) quitting all other sports to focus on 1 sport, and (3) year-round training (greater than 8 months per year). A number of sports medicine organizations have published recommendations based on the limited evidence available on this topic. The objective of this article was to perform a narrative review of the currently available evidence and sports medicine organizational recommendations regarding sport specialization and its effects on health to guide athletic trainers and sports medicine providers. To accomplish this goal, we conducted a narrative review of articles and position statements on sport specialization published from 1990 through 2018. Injury, overuse injury, serious overuse injury, and lower extremity injury were likely associated with higher degrees of sport specialization in various populations. Sports medicine organizations in general recommended against sport specialization in young athletes and instead promoted multisport participation for physical and psychological benefits. Few long-term data suggest that sport specialization has negative health-related quality-of-life consequences. Higher degrees of sport specialization likely pose risks of overuse injury; however, the age of specialization at which this risk occurs is not known. Because different populations and sports activities may put children at risk for certain injuries, future researchers should monitor large populations with sport-specific prospective active surveillance.